Body composition, functional and performance characteristics in top Czech young athletes - Bunc, V.; Hráský, P.; Baláš, J. (Academic Coordination Centre Journal, 2011)
The actual motor performance and thus the actual state of physical fitness of subjects is partly a consequence of their genetic predisposition and partly a consequence of the moving training they undertake. The basic problem by interpretation of exercise testing results in young subjects is a determination of actual (biological) state of subjects. Body composition (BC) may be used as a criterion of their development state. Dependence between selected maximal variables (maximal oxygen uptake per kg body mass - VO2max.kg-1, calculated total work - CTW, and maximal power output - MPO), and BC (%BF, FFM, BCM and ECM/BCM) were studied in a group of 665 top Czech young athletes (433 boys and 232 girls) of different sports events in age ranged from 10 to 18 years. The functional variables were assessed by incremental treadmill test. According to our results we present the basic physiological predispositions for success in some sports in both - boys and girls at the age of 15. These data play a decisive role in the selection of talent for the particular sports event.